PSYCHOLOGICAL PREPARATION OF JUDO ATHLETES FOR COMPETITIONS (International journal of artificial intelligence, 2025)
The psychological preparation of judo athletes plays a crucial role in enhancing their performance in competitive environments. Judo, being a mentally demanding sport, requires athletes to maintain mental resilience, focus, emotional control, and confidence throughout their training and competitions. Psychological strategies such as mental toughness, concentration, visualization, and goal setting help athletes prepare for the challenges of high-pressure situations. Additionally, emotional regulation techniques, including breathing exercises and coping strategies, enable athletes to manage stress and adversity effectively. This paper discusses the various components of psychological preparation and their application in competitive judo, emphasizing the importance of developing a strong mental game to complement physical training and maximize performance outcomes.